2013
DOI: 10.1128/jvi.00174-13
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Suppresses C9 Complement Synthesis and Impairs Membrane Attack Complex Function

Abstract: Hepatitis C virus (HCV) proteins inhibit complement component expression, which may attenuate immunity against infection. In this study, we examined whether HCV regulates the membrane attack complex (MAC) via complement component C9. MAC is composed of C5b to C9 (C5b-9) and mediates cell lysis of invaded pathogens. Liver biopsy specimens from chronically HCVinfected patients exhibited a lower level of C9 mRNA expression than liver biopsy specimens from unrelated disease or healthy control human liver RNA. Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…The role of the complement system in the pathogenesis of AMD has been studied and reviewed extensively over the past decade (Warwick et al, ; Bora et al, ; McHarg et al, ). Key facts supporting the role of the complement system in the pathogenesis of AMD include the following: (i) Several complement components have been detected in drusen and AMD lesions (Anderson et al, , ); (ii) higher plasma levels of C3a, C3d, Bb, and C5a have been observed in AMD patients (Scholl et al, ; Reynolds et al, ; Lechner et al, ); (iii) polymorphisms in a number of complement genes (CFH, CFB, C2, SERPING1, and C3) are genetic risk factors of AMD (Edwards, ; Cipriani et al, ); and (iv) inhibition of complement suppresses laser‐induced CNV in mice (Nozaki et al, ; Bora et al, ; Kim et al, ; Lipo et al, ). Mechanistically, CFH may inhibit CD47‐mediated resolution of subretinal inflammation and this inhibitory effect could be enhanced by the AMD associated CFH (H402) variant (Calippe et al, ).…”
Section: Targeting the Complement System In Retinal Degenerative Disementioning
confidence: 99%
“…The role of the complement system in the pathogenesis of AMD has been studied and reviewed extensively over the past decade (Warwick et al, ; Bora et al, ; McHarg et al, ). Key facts supporting the role of the complement system in the pathogenesis of AMD include the following: (i) Several complement components have been detected in drusen and AMD lesions (Anderson et al, , ); (ii) higher plasma levels of C3a, C3d, Bb, and C5a have been observed in AMD patients (Scholl et al, ; Reynolds et al, ; Lechner et al, ); (iii) polymorphisms in a number of complement genes (CFH, CFB, C2, SERPING1, and C3) are genetic risk factors of AMD (Edwards, ; Cipriani et al, ); and (iv) inhibition of complement suppresses laser‐induced CNV in mice (Nozaki et al, ; Bora et al, ; Kim et al, ; Lipo et al, ). Mechanistically, CFH may inhibit CD47‐mediated resolution of subretinal inflammation and this inhibitory effect could be enhanced by the AMD associated CFH (H402) variant (Calippe et al, ).…”
Section: Targeting the Complement System In Retinal Degenerative Disementioning
confidence: 99%
“…(30,33) Complement activation upon HCV infection has been implicated in several studies. (34)(35)(36) In addition, CD55 and CD59, regulators of complement activation, were shown to be incorporated into HCV virions, (37,38) which led to resistance to complement-mediated, antibody-dependent virolysis. In the present study, we demonstrated that HCV particles produced either by in vitro cell culture system or directly from chronic HCV patients were opsonized but not lysed by complement activation, which eventually led to preferential association of HCV particles with B cells in PBMCs.…”
Section: Figmentioning
confidence: 99%
“…HCV impairs C4 and C3 synthesis in infected subjects . C9 is significantly reduced (≥20‐fold) at messenger RNA level in chronically HCV‐infected liver biopsy specimens, while many hepatocyte‐derived complement components (C6, C8, Factor B, MASP1, and MBL) remain mostly unaffected . C3 acts as a link between innate and adaptive immunity and is important for B cell activation and T cell–dependent antibody responses.…”
Section: Resultsmentioning
confidence: 99%